Clinical Correlation of Risk Factors for the development of Bilirubin Encephalopathy in Neonatal and Postneonatal Children - Mekhrgiyo Khushmurodova; Yokutkhan Madjidova; Dilnoza Iskhandarova; Farrux Samatov; Abdulvokhid Amiriddinov; Jonibek Toxirov (International Journal of Medical Toxicology and Legal Medicine, 2024)
Jaundice and its pathological manifestations cause neurological disorders in children in the neonatal and post-neonatal period. According to the World Health Organization, the prolongation of neonatal jaundice or its pathological forms are developing, even among developed countries. sometimes causing neurological complications.In order to study the risk factors for the development of bilirubin encephalopathy in children in the neonatal and post-neonatal period, 80 babies with hyperbilirubinemia in the neonatal and post-neonatal period were selected from the department of infant resuscitation and pathology of newborn babies of the Perinatal Center of Surkhandarya Region. In order to determine the cause and development factors of bilirubin encephalopathy, the mother's age, hereditary diseases, epidemiological history, as well as somatic diseases of the mother, obstetric-gynecological history, the course of pregnancy and childbirth complications, the course of childbirth were studied. General blood analysis, biochemical analysis of blood: bilirubin and its fractions determine the level and course of complications of bilirubin intoxication. Bilirubin and its fractions in the blood analysis of each examinee were checked and monitored several times, because bilirubin and its fractions are important for the acute or chronic course of the disease and neurological disorders. evaluates the condition. Diagnosis of bilirubin encephalopathy, clinical-neurological status, prognosis and complications are inextricably linked with clinical-laboratory aspects. Pathological course of pregnancy: severe level of anemia, severe form of toxicosis, numerous abortions and urogenital diseases, maternal hypertension, endocrinopathies, intra-fetal infection and long-lasting gestosis create conditions for bilirubin intoxication and aggravate damage to the hematoencephalic barrier of the brain. resulting in increased toxic effects of bilirubin.